NKT-associated hedgehog and osteopontin drive fibrogenesis in non-alcoholic fatty liver disease. Issue 9 (17th March 2012) - Syn, Wing-Kin; Agboola, Kolade M; Swiderska, Marzena; Michelotti, Gregory A; Liaskou, Evaggelia; Pang, Herbert; Xie, Guanhua; Philips, George; Chan, Isaac S; Karaca, Gamze F; Pereira, Thiago de Almeida; Chen, Yuping; et al.
Abstract : Objective: Immune responses are important in dictating non-alcoholic steatohepatitis (NASH) outcome. We previously reported that upregulation of hedgehog (Hh) and osteopontin (OPN) occurs in NASH, that Hh-regulated accumulation of natural killer T (NKT) cells promotes hepatic stellate cell (HSC) activation, and that cirrhotic livers harbour large numbers of NKT cells. Design: The hypothesis that activated NKT cells drive fibrogenesis during NASH was evaluated by assessing if NKT depletion protects against NASH fibrosis; identifying the NKT-associated fibrogenic factors; and correlating plasma levels of the NKT cell-associated factor OPN with fibrosis severity in mice and humans. Results: When fed methionine-choline-deficient (MCD) diets for 8 weeks, wild type (WT) mice exhibited Hh pathway activation, enhanced OPN expression, and NASH-fibrosis. Ja18‒/‒ and CD1d‒/‒ mice which lack NKT cells had significantly attenuated Hh and OPN expression and dramatically less fibrosis. Liver mononuclear cells (LMNCs) from MCD diet fed WT mice contained activated NKT cells, generated Hh and OPN, and stimulated HSCs to become myofibroblasts; neutralising these factors abrogated the fibrogenic actions of WT LMNCs. LMNCs from NKT-cell-deficient mice were deficient in fibrogenic factors, failing to activate collagen gene expression in HSCs. Human NASH livers with advanced fibrosis contained more OPN and Hh protein than those with early fibrosis. Plasma levels of OPN mirrored hepatic OPN expression and correlated with fibrosis severity. Conclusion: Hepatic NKT cells drive production of OPN and Hh ligands that promote fibrogenesis during NASH. Associated increases in plasma levels of OPN may provide a biomarker of NASH fibrosis.